“A Little Unspoilt Paradise”: Profile and Practices of Tourism-Related Lifestyle Migrant Entrepreneurs in Southern Portugal - Filipa Perdigão Ribeiro; Kate Torkington; Sandra Rebelo (Journal of Tourism, Sustainability and Well-being)
This paper investigates the potential of the fairly recent phenomenon of entrepreneurial lifestyle migration, in the context of rural Algarve (Portugal) from the perspective of lifestyle migrant entrepreneurs (LMEs) and their socioeconomic contribution to the development of rural areas. The study focuses on the profile of LMEs who are active in tourism businesses, by analysing the results of an online survey with a sample of 60 business owners and semi-structured interviews with 16 representatives of local councils. Findings show that these LMEs are well-settled, intend to stay and invest in the future. Despite facing complex challenges, including push factors such as bureaucratic obstacles and language barriers, results reveal that lifestyle orientations remain a priority. We argue that if the potential for tourism-related LMEs to contribute with sustainable practices to support tourism development is to be realised, public efforts to support these communities need to be stable and long term.